Numerical Evaluation of Cushioning Pressure in Water Entry of Rigid Bodies - Mojtaba Barjasteh; Hamid Zeraatgar (International Journal of Maritime Technology, 2017)
Effect of air cushion layer right before impact of a rigid body onto water surface has been investigated in this paper. The study is mainly focused on evaluation of cushioning pressure and the resulting free surface elevation. The air flow is assumed to be an irrotational flow which is governed by Laplace equation. The air problem and the resulting response of the water free surface are supposed to be weakly coupled because of very low air pressure. Integral equation for each medium has been numerically solved separately using boundary element method. The problem is assumed to be unsteady with a constant body speed. The numerical results have been also compared with analytical method which shows a fair agreement. Results show that the geometry of impacting body and particularly its bluntness are the primary affecting parameter which can dramatically influence the free surface profile and air pressure. Such a behavior has been observed for two different geometries, ellipse and wedge section, having identical breadth.